PENERAPAN STRATEGI THINK TALK WRITE DALAM PEMBELAJARAN KOOPERATIF UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PESERTA DIDIK KELAS X MIA SMA NURUL FALAH PEKANBARU - Sandy, Aulia; Saragih, Sehatta; Hutapea, Nahor Murani (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to improve the learning process and increase the student?s mathematics learning outcomes through the implementation of the Think-Talk-Write Strategy in Cooperative Learning. This type of research is the Classroom Action Research with two cycle. The research was conducted in class X MIA SMA Nurul Falah Pekanbaru in the second semester of the 2018/2019 academic year with the subject of as many as 16 students, consist of 5 boys and 11 girls. The research instrument consists of learning devices and instrument data collectors. Learning device used in this research is the Syllabus, Lesson Plan and Worksheet. The instrument data collector used in this research is the observation sheet and math achievement test. Data analysis technique used is descriptive statistical analysis. Based on the result of the research showed that implementation of learning process on cycle II had happened improvement from implementation on cycle I. Weakness on cycle I is improved on implementation cycle II according with planning of improvement after reflection cycle I. Number of students that reach Minimum Mastery Criteria increase from basic score to daily test II. The number of students who reach Minimum Mastery Criteria on basic scor, daily test I and daily test II are respectively 6 person (37,5%), 8 person (50%) and 12 person (75%). Results of this research indicates that application of the Think-Talk-Write Strategy in Cooperative Learning can improve learning process and increase mathematics learning outcomes from the students at class X MIA SMA Nurul Falah Pekanbaru in the second semester academic years 2018/2019 in matery of Trigonometry.Key Words: Cooperative Learning, Think Talk Write Strategy, Learning Process, Student?s Mathematics Learning Outcomes, Classroom Action Research.